Implementasi Komunikasi Pemasaran Lembaga Pendidikan Informal “Seaman’s English Education Indonesia ” - Aldi Satrio Herlambang (Fakultas Ilmu Komunikasi Universitas Pancasila, 2018)
Seaman’s English Education Indonesia (SEE Indonesia) is an informal educational institution located in North Jakarta that offers a variety of courses for seafarers, mainly the Marlins Test course, and an English language test for seafarers. Because it’s new, it is fitting that the level of brand awareness by consumers is still very low. Based on data from customer visits in SEE Indonesia per year since its inception, only 768 people have visited SEE Indonesia, whether they only came or used the services of courses. This number is still very small compared to the total number of Indonesian seafarers, which are around 850,000. Therefore a marketing communication program is needed so that SEE Indonesia can increase brand awareness and win the market from its competitors. In order to increase the brand awareness of SEE Indonesia, then in this work the writer will use the Participatory Action Research method, where this method will involve people involved in existing problems to actively participate so that they are expected to get a solution right. The results of the Participatory Action Research will then become information material for the SOSTAC theory that will be used to create the SEE Indonesia marketing communication program.